Nanoporous organic field-effect transistors employing a calixarene dielectric for sub-ppb gas sensing - Tisserant, Jean-Nicolas; Beck, Sebastian; Kowalsky, Wolfgang (Advanced electronic materials, 2018)
The increase of exposure to volatile organic compounds in general, and endocrine disruptors in particular, through daily healthcare consumer goods urgently calls for the development and commercialization of cheap and easy-to-use sensors to detect these molecules in air. Organic semiconductors (OSCs) promise the mass fabrication of cheap and flexible sensors, under the condition that the fabrication of functional thin films having the right morphology can be fully harnessed. Nanoporous morphologies are interesting in the field of gas sensing because they facilitate the diffusion of gas molecules to the active volume of organic field-effect transistors (OFETs), at the vicinity of the gate dielectric. Nanoporous films of OSCs are, however, challenging to produce and to transfer into working sensors. Usage of nanoporous OSC films deposited on a sensitive 4-tert-butylcalix[6]arene gate dielectric as the active layer of an OFET-based gas sensor is proposed here. The semiconducting molecules are self-assembled into nanoporous films at the interface between air and water, allowing their transfer to practically any gas-sensitive dielectric substrate. The OFET built on this film stack is used here to sense the presence of methyl 4-hydroxybenzoate (methylparaben) in air at concentrations below 1 ppb.
Gesehen am 08.08.2019